New practices to prevent knowledge management projects or programs failure in an organization: a systematic literature review / Alwi Mohd Yunus ... [et al.] - Mohd Yunus, Alwi; Zakaria, Norizan; Kamarulzaman, Mohd Ridwan; Abd Kadir, Irwan Kamarudin; Rafedzi, E. R. K. (Faculty of Information Management, 2024)
Knowledge management is a set of dynamic and continuing activities as well as practices grounded in individual and social structures. It is all about how companies organize, store, and share what they know. The primary objective of knowledge management is to ensure that accessible knowledge is employed to the benefit of the organization. This study is based on a systematic literature review as an evaluation as well as interpretation of 13 articles on knowledge management to prevent projects or program failure from EBSCO and ScienceDirect. This review identified five major latest practices related to knowledge management namely organizational learning, technology, acquisition and dissemination of knowledge, knowledge sharing, and knowledge organization. Future studies should be conducted on knowledge management in different types of organizations, which can then prompt more detailed research on organizational and technology-driven companies.